Milk - Cohen, Bruce; Jinks, Dan; London, Michael; Black, Dustin Lance; Van Sant, Gus; Penn, Sean, 1960-; Hirsch, Emile, 1985-; Brolin, Josh; Luna, Diego, 1979-; Franco, James, 1978-; Pill, Alison, 1985-; Garber, Victor (Focus Features four-star collection, 2009)
His life changed history, his courage changed lives. Harvey Milk is a middle-aged New Yorker who, after moving to San Francisco, becomes a Gay Rights activist and city politician. On his third attempt, he is elected to San Francisco's Board of Supervisors in 1977, the first openly-gay man to be elected to public office in the United States. The following year, both he and the city's mayor, George Moscone, are shot to death by former city supervisor, Dan White, who blames his former colleagues for denying White's attempt to rescind his resignation from the board. Based on the true story of Harvey Milk.